The combination of granulocyte‐monocyte apheresis and vedolizumab: A new treatment option for ulcerative colitis?. Issue 6 (13th September 2019) - Rodríguez‐Lago, Iago; Benítez, José M.; Sempere, Laura; Sáez‐González, Esteban; Barreiro‐de Acosta, Manuel; de Zárate, Jone O.; Cabriada, José L.
Abstract: Objectives: To assess the effectiveness and safety of combining granulocyte‐monocyte apheresis (GMA) and vedolizumab (VDZ) in patients with refractory ulcerative colitis (UC). Methods: This retrospective, multicentre pilot study included all UC patients receiving both GMA and VDZ. We recorded data on GMA sessions, demographic characteristics, and clinical response. Effectiveness was assessed 1 and 6 months after finishing the GMA using the partial Mayo score, C‐reactive protein, and fecal calprotectin levels. Data were also compiled on VDZ intensification, use of new immunomodulators and colectomy during follow‐up. Results: Eight patients were included (mean age 46 years; 63% female; mean disease duration, 132 months; 50% E3). GMA was started after a loss of response to VDZ in all cases (25% primary nonresponse and 75% secondary loss of response). All had previously received anti‐TNF agents. VDZ was prescribed as the second‐, third‐, or fourth‐line biologic in 37%, 50%, and 13% of cases, respectively. Patients had a mean baseline partial Mayo score of 7.5 (SD 2.1) and received a median of 15 GMA sessions (range 5‐38). After a median follow‐up of 7.5 months (IQR 5‐12), partial Mayo score decreased after 1 and 6 months ( P = .01 and .06, respectively). Three patients (38%) achieved steroid‐free clinical remission and five (63%) withdrew VDZ. Colectomy rate was 38%. No adverse events were observed during the combination therapy. Conclusions: This small case series suggests that combining GMA with VDZ could be a treatment option in selected cases of UC with an inadequate response to this biologic agent.